Influence of Zinc on the yield and nutrition of wet season rice (Oryza sativa) grown under aeric endoaquept - ROY, PRIYAMA; DAS, D K; DOLUI, A K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment on wet season kharif rice (Oryza sativa L.) cv IET 4094 was conducted during the year 2010- 11 and 2011-12 in an aeric endoaquept to study the influence of applied zinc on the growth, yield and nutrition of rice. The results show that the application of chelated zinc (Zn-EDTA) increased N, P, K and Zn concentration in dry matter and grains of rice. The highest amount of N, P,K and Zn in rice dry matter and grain have been found to be recorded in the treatment where the recommended levels of NPK (80:40:40) and chelated zinc in two splits (one at basal and the second one at grand tillering stage) were applied. The percent increase in the yield of grain (43.20) and straw (68.50) were also recorded highest in the treatment where Zn-EDTA was applied in two splits (0.5 kg/ha as basal + 0.5 kg/ha at grand tillering stage) over that of the control, while that of the same percent increase of the applied Zn–EDTA was highest in rice grain yield (18.40) over that of the corresponding highest level of ZnSO4.7H2O (20 kg/ha) at two splits.